Sport Participation And Peer Group Influence In Basketball Education: A Systematic Review Of Sociological Perspectives - Tri Angriawan (Journal of Sport Education, Coaching, and Health (JOCCA), 2026)
Sport participation in educational settings has received increasing attention because of its contribution to students’ physical, psychological, and social development. Among various sports, basketball provides a unique social environment that promotes teamwork, communication, cooperation, and collective identity formation. However, students’ participation in basketball is not solely influenced by individual motivation but is also shaped by sociological factors, particularly peer-group influence. Therefore, this study aimed to systematically review and synthesize empirical and conceptual evidence regarding the relationship between sport participation and peer-group influence in basketball education from sociological perspectives. This study employed a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. Literature was collected from Scopus, Web of Science, ERIC, PubMed, Google Scholar, SINTA, DOAJ, and Garuda databases. Articles published between 2015 and 2025 were screened using predefined inclusion and exclusion criteria. A total of 187 records were initially identified, and after the screening and eligibility process, 25 studies were included in the final synthesis. The findings revealed that peer support (88%) was the most influential sociological factor affecting basketball participation, followed by team cohesion (76%), social identity (68%), friendship networks (60%), and social capital (44%). Furthermore, peer support positively contributed to participation intention (81%), attendance consistency (78%), sport commitment (76%), learning motivation (74%), and basketball enjoyment (72%). The findings support Social Learning Theory, Social Identity Theory, Social Capital Theory, and the Social Ecological Model in explaining students’ participation behavior. In conclusion, peer-group dynamics play a decisive role in enhancing basketball participation and sustaining engagement in educational settings. Developing supportive peer environments and cohesive team cultures can significantly improve students’ participation and educational outcomes in basketball programs.